2010
DOI: 10.1177/0267323110363652
|View full text |Cite
|
Sign up to set email alerts
|

Towards a European identity? The news media and the case of climate change

Abstract: Much research on the discursive construction of Europe in national news media has quantitatively focused on the presence of ‘EU topics’. The more frequently EU topics appear, the better the breeding-ground for a sense of European community, it is argued. This article tackles the question of a European identity from a different angle. Guided by theories on collective identity and power, and utilizing qualitative discourse analysis of the reporting on climate change in a tabloid newspaper and public service tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 22 publications
(24 reference statements)
0
64
0
2
Order By: Relevance
“…Moreover, these studies have shown that in national public spheres dominated by Eurosceptic media reporting, journalists portrayed a deep sense of doubt regarding the EU's ability to convince states such as the US or China to agree to a progressive global agreement that could effectively tackle climate change. The EU's failure at the Copenhagen summit was perceived by the UK or Swedish media as a sign that their states would be more effective acting unilaterally rather than through the common framework of the European Union Marshall 2011, 1138;Olausson 2010;). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these studies have shown that in national public spheres dominated by Eurosceptic media reporting, journalists portrayed a deep sense of doubt regarding the EU's ability to convince states such as the US or China to agree to a progressive global agreement that could effectively tackle climate change. The EU's failure at the Copenhagen summit was perceived by the UK or Swedish media as a sign that their states would be more effective acting unilaterally rather than through the common framework of the European Union Marshall 2011, 1138;Olausson 2010;). …”
Section: Introductionmentioning
confidence: 99%
“…Some SRT researchers of climate change have begun to do this (e.g. Höijer, 2010;Olausson, 2010Olausson, , 2011. Moscovici (1988) has postulated three types of social representation: hegemonic, emancipated and polemic.…”
Section: Constructors Of Social Representationsmentioning
confidence: 99%
“…Existing SRT research into climate change communication suggests the existence of some key social representations in Western industrialised societies (Höijer, 2010;Olausson, 2010Olausson, , 2011Smith & Joffe, 2013. The notion that anthropogenic climate change is largely a human-induced environmental problem constitutes a hegemonic representation, which has been encouraged since at least 1988 .…”
Section: A Key Social Representation Of Climate Changementioning
confidence: 99%
“…From a discourse theoretical perspective, an emergent trajectory of the research field (Cottle, 2009), "global" is instead understood as a discursive feature. From this point of view it could be argued that global media cannot be reduced to transnational media networks; a global discourse might develop in any kind of media, be it local, national, or transnational, as well as in any kind of media content -local, domestic, or foreign (Berglez, 2008;Olausson, 2010). Any medium might, in fact, be labeled "global" if it provides its audiences with a global interpretative framework.…”
mentioning
confidence: 99%
“…I will develop this position first by examining the arguments of the line of research that equates global media with transnational media networks, including its contradictory arguments about the ability of these networks to contribute to or be part of globalization processes. Following this, the discourse perspective will be introduced and exemplified with some empirical examples from a study on the emergence of a transnational (European) identity in national news reporting on global climate change (Olausson, 2010). The chapter ends with a discussion in which the discourse theoretical approach is put in relation to broader issues of cultural and political transformation, conclusions are drawn about the media's relationship to globalization processes, and suggestions are made for an integral explanation of global media.…”
mentioning
confidence: 99%